Effectiveness of Audio-Visual Aids in Teaching English as a Foreign Language at the University Level (Journal of Human Sciences, 2023)
The purpose of this study is to investigate to what extent the widespread use of audio-visual aids with Libyan EFL university instructors. Also, it is to examine how such audio-visual aids are appropriate to Arabic-speaking Libyan undergraduate students specializing in the English language as to be teachers of English after graduation.  A combination of quantitative and qualitative approaches for collecting data was followed. The quantitative approach was based on a closed-ended questionnaire to check Libyan EFL university instructors’ opinions towards using audio-visual aids within the class whereas the qualitative approach was based on observations to notice the effectiveness of audio-visual aids in the class. Thirty four Libyan EFL university instructors participated in filling in the questionnaire sent via personal e-mails and Facebook messenger. This was followed by twenty four undergraduate students at Tripoli University (Faculty of Education – Department of English) who were observed while attending lectures on Listening and Speaking. The obtained results of the study showed how audio-visual aids had a strong effect on students' interaction. The implications of this study suggest that Libyan EFL university instructors have to consider audio-visual aids as a means to motivate students’ interactions. They are highly recommended to focus on the integration of audio-visual aids in teaching foreign languages.